Towards a continuum thermodynamics framework for mechanism-based modelling of oxidative ageing in bitumen. Issue Volume 21:Issued 11(2020) (18th September 2020) - Mühlich, Uwe
ABSTRACT: A reaction–diffusion framework for modelling oxidative ageing in bitumen is derived from thermodynamics of irreversible processes. The link between continuum scale and molecular level is established through an activity model based on solubities and molar volumes. General features are demonstrated exemplary for the so-called 'spurt oxidation process'. Key aspects of the corresponding model are discussed by means of film ageing simulations.